An Empirical Assessment Of The Central Bank Of Nigeria's (CBN) Policy is Used to Analyze the Factors That Influence Monetary Policy and the Stability Of Nigeria's Economic Growth. - Sulaiman, T.H; Ajiteru, S.A.R; Abalaka, J.N (Global Economics: International Journal of Economic, Social and Development Sciences, 2025)
This study examines the impact of the Central Bank of Nigeria's monetary policies on the Nigerian economy, specifically how these policies can be applied to foster economic growth. The research employs multiple regression models as the primary statistical method to analyze the relationship between key variables: money supply, average price levels, interest rates, labor force, and their effects on the Gross Domestic Product (GDP). Using data from 1981 to 2008, the study applies the Ordinary Least Squares (OLS) method to assess these effects comprehensively. The findings indicate that monetary policy, as reflected by money supply, positively influences GDP growth and improves the balance of payments, while also having a negative impact on inflation rates. The study suggests that the Nigerian money market should introduce a broader range of financial instruments to cater to the growing economy’s needs. Additionally, the recommendations emphasize the importance of designing monetary policies that create a favorable investment climate by adjusting interest rates, currency rates, and liquidity management mechanisms. By fostering a well-regulated and flexible monetary system, the Central Bank can further enhance the economic stability and growth of Nigeria, supporting sustainable development in the long term.